Electrical Tunability in 3-Gated Reconfigurable Transistor for Analog/RF Applications - Chinmayi Adoni; Sandeep Semwal; Manish Gupta; Jean-Pierre Raskin; Abhinav Kranti (IEEE Journal of the Electron Devices Society, 2025)
The potential of electrical tunability in a 3-gated (3G) Reconfigurable Field Effect Transistor (RFET) for analog/RF applications is investigated through four distinct configurations (R ${}_{\text {2-IG-LVT}}$ , R ${}_{\text {1-IG-Ambi}}$ , R ${}_{\text {3-IG-LVT}}$ , and R ${}_{\text {2-IG-HVT}}$ ). The electrical connections through two program gates (PG) and one control gate (CG) in 3G-RFET supports the implementation of configurations suitable for low-VTH (R ${}_{\text {2-IG-LVT}}$ and R ${}_{\text {3-IG-LVT}}$ ) and high-VTH (R ${}_{\text {2-IG-HVT}}$ ), phase follower/reversal (R ${}_{\text {2-IG-LVT}}$ ), frequency doubler (R ${}_{\text {1-IG-Ambi}}$ ), high gain (R ${}_{\text {3-IG-LVT}}$ ), lower parasitic capacitance (R ${}_{\text {2-IG-LVT}}$ and R ${}_{\text {3-IG-LVT}}$ ), and higher linearity (R ${}_{\text {3-IG-LVT}}$ ) applications. Results showcase electrical tunability as an opportunity to realize many analog/RF features–in–one nanoscale 3G-RFET.